Quasi‐Freestanding Graphene on SiC(0001) by Ar‐Mediated Intercalation of Antimony: A Route Toward Intercalation of High‐Vapor‐Pressure Elements. Issue 11 (22nd August 2019) - Wolff, Susanne; Roscher, Sarah; Timmermann, Felix; Daniel, Marcus V.; Speck, Florian; Wanke, Martina; Albrecht, Manfred; Seyller, Thomas
Abstract: A novel strategy for the intercalation of antimony (Sb) under the (6 3 × 6 3 ) R 30 ° reconstruction, also known as buffer layer, on SiC(0001) is reported. Using X‐ray photoelectron spectroscopy, low‐energy electron diffraction, and angle‐resolved photoelectron spectroscopy, it is demonstrated that, while the intercalation of the volatile Sb is not possible by annealing the Sb‐coated buffer layer in ultrahigh vacuum, it can be achieved by annealing the sample in an atmosphere of Ar, which suppresses Sb desorption. The intercalation leads to a decoupling of the buffer layer from the SiC(0001) surface and the formation of quasi‐freestanding graphene. The intercalation process paves the way for future studies of the formation of quasi‐freestanding graphene by intercalation of high‐vapor‐pressure elements, which are not accessible by previously known intercalation techniques, and thus provides new avenues for the manipulation of epitaxial graphene on SiC. Abstract : The intercalation of various elements under the buffer layer on SiC(0001) leads to the formation of so‐called quasi‐freestanding graphene. Using the example of antimony, a novel process based on thermal annealing in an atmospheric‐pressure argon environment is introduced, that allows the intercalation of high‐vapor‐pressure elements for which intercalation was not possible by previously established techniques.